Rethinking food and agriculture : new ways forward - Kassam, A. H.; Kassam, Laila (Woodhead Publishing, 2021)
Given the central role of the food and agriculture system in driving so many of the connected ecological, social and economic threats and challenges we currently face, Rethinking Food and Agriculture reviews, reassesses and reimagines the current food and agriculture system and the narrow paradigm in which it operates. Rethinking Food and Agriculture explores and uncovers some of the key historical, ethical, economic, social, cultural, political, and structural drivers and root causes of unsustainability, degradation of the agricultural environment, destruction of nature, short-comings in science and knowledge systems, inequality, hunger and food insecurity, and disharmony. It reviews efforts towards 'sustainable development', and reassesses whether these efforts have been implemented with adequate responsibility, acceptable societal and environmental costs and optimal engagement to secure sustainability, equity and justice. The book highlights the many ways that farmers and their communities, civil society groups, social movements, development experts, scientists and others have been raising awareness of these issues, implementing solutions and forging 'new ways forward', for example towards paradigms of agriculture, natural resource management and human nutrition which are more sustainable and just.